Tongue-in-Groove technique for Reconstruction of Nasal Tip Ptosis due to Rhinoplasty, A Cross-Sectional Study - Khoshsirat, Shahrokh; soroureddin, Zahra; Shiravand, Sepideh (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2020)
Background: nasal tip ptosis is believed to be one of the most common nasal malformations with a relatively high prevalence in patients who underwent rhinoplasity operation. A variety of techniques has been defined for the surgical modification of tip ptosis. The TIG technique seems to be a multipurpose surgical approach for the modification of nose in the lower third region. TIG could be appropriate in the primary and most modified cases and to show better results, it has been integrated with other surgical systems. Aim: The aim of this study is to investigate TIG technique in patients with nasal tip ptosis after Rhinoplasty, referring to Loghman-E- Hakim hospital, Tehran, Iran. Methods: In following descriptive cross-sectional study, surgical operation was carried out in thirty-three patients suffering from nasal tip ptosis between 2012 and 2013 using the described technique. The data were gathered in a questionnaire designed for this purpose. At the end, the degree of nasal ptosis was determined in these patients. Results: In this study, nasal shape was desirable in 75.7% of patients and there was no case of nasal ptosis. 82.8% of the patients were satisfied with the results. 81.1% of patients have not any complications. Other factors did not associate with nasal ptosis (P> 0.05). Conclusion: based on the results of this study and their comparison with other studies conducted in this field, TIG method after rhinoplasty can reduce nasal ptosis. Thus, it can be deduced they will be proper in the both primary and most revision cases.